Genetic variability in cultivated common bean beyond the two major gene pools - Islam, F.M.A.; Basford, KE; Redden, R.J.; González, A.V.; Kroonenberg, PM; Beebe, Stephen E. (Springer, 2002)
It is generally accepted that two major gene pools exist in cultivatedcommon bean (Phaseolus vulgaris L.), a MiddleAmerican and an Andean one. Some evidence, based on unique phaseolin morphotypesand AFLP analysis, suggests that at least one more gene pool exists incultivated common bean. To investigate this hypothesis, 1072 accessions from acommon bean core collection from the primary centres of origin, held at CIAT,were investigated. Various agronomic and morphological attributes (14categorical and 11 quantitative) were measured. Multivariate analyses,consisting of homogeneity analysis and clustering for categorical data,clustering and ordination techniques for quantitative data and nonlinearprincipal component analysis for mixed data, were undertaken. The results ofmost analyses supported the existence of the two major gene pools. However, theanalysis of categorical data of protein types showed an additional minor genepool. The minor gene pool is designated North Andean and includes phaseolintypes CH, S and T; lectin types 312, Pr, B and K; and mostly A5, A6 and A4 types?-amylase inhibitor. Analysis of the combined categorical data ofprotein types and some plant categorical data also suggested that some othergermplasm with C type phaseolin are distinguished from the major gene pools.